IMPLEMENTASI DATA MINING ROUGH SET DALAM MENENTUKAN TINGKAT KERUSAKAN ALAT DAN BAHAN KIMIA (STUDI KASUS DI LABORATORIUM RESEP SMK S-16 FARMASI BENGKULU) - Marnis Nasution (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2019)
Data mining is one of the methods used in extracting the data in generating new knowledge fromstored data. The extent of damage to the equipment and chemicals that affect the cost of school often donot know how much it cost the school. With data mining that generates knowledge in the form of somerules and help the school to predict the extent of damage and the cost of chemicals that can be in.